Financing of the Infrastructure Development in Cambodia - Tomasz LUKASZEWSKI (Communications of International Proceedings, 2020)
In the 1990s Cambodia was practically deprived of the infrastructure. The reconstruction and development of new physical facilities required substantial expenditures, exceeding the capabilities of a war-ravaged country lacking of money, industry, specialists and resources. To overcome an insufficiency of public financial and material assets, government had to encourage external capital to involvement in the provision of infrastructure projects. The aim of the paper is to analyse the case of Cambodia to examine mechanisms of financing the infrastructure investments in developing countries. The article addresses two issues. Firstly, reviews the political, regulatory and legal actions taken by the government to establish business climate conductive to investment and attractive to investors. Secondly, attempts to assess the effectiveness of those measures by analyse the structure and dynamics of capital expenditures on infrastructure development in Cambodia in 2006-2018. The research used descriptive method and quantitative data obtained from documents published by public entities.
Keywords: Infrastructure; Cambodia; development; public investment; private investment.